Final report of the simplification and harmonization of the customs procedures in the Caribbean Common Market using the Kyoto Convention - John, C.M. (CEDP St. Michael, BarbadosBB, 1991)
Describes tenets of the Kyoto Convention. Points out the benefits to be derived from accession to it but also advances arguments against accession. Lists annexes of the Convention which were adopted by the Customs Cooperation Council and compares them with legislation from CARICOM Member States. Recommends that CARICOM States accede to the Convention.